2017
DOI: 10.1021/acs.jafc.7b04233
|View full text |Cite
|
Sign up to set email alerts
|

Short-Chain Fatty Acids Suppress Inflammatory Reactions in Caco-2 Cells and Mouse Colons

Abstract: Short-chain fatty acids (SCFAs), such as acetate, propionate, and butyrate, play an important role in the maintenance of intestinal homeostasis. In the present study, anti-inflammatory effects of SCFAs were examined in human intestinal Caco-2 cells and mouse colonic cultures. Stimulation of Caco-2 cells with tumor necrosis factor (TNF)-α induced interleukin (IL)-8 (TNF-α, 17.1 ± 7.2 vs Control, 1.00 ± 0.26, P < 0.01) and IL-6 expression (TNF-α, 21.7 ± 10.0 vs Control, 1.00 ± 0.28, P < 0.01) through the activat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
41
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(49 citation statements)
references
References 51 publications
5
41
1
2
Order By: Relevance
“…Short chain fatty acids have also been shown to have anti-inflammatory activity in immune cells [5,7], however, effects on intestinal host cells are not well understood. Interleukins (ILs) are secreted cytokines that regulate immune responses and can function in a pro-or antiinflammatory manner.…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…Short chain fatty acids have also been shown to have anti-inflammatory activity in immune cells [5,7], however, effects on intestinal host cells are not well understood. Interleukins (ILs) are secreted cytokines that regulate immune responses and can function in a pro-or antiinflammatory manner.…”
Section: Plos Onementioning
confidence: 99%
“…Short chain fatty acids are also known to exhibit effects on cellular proliferation and immune response [5]. Previous literature has shown that BUT decreases cellular proliferation and increases antimicrobial peptide expression, cytokine/ chemokine production, as well as tight junction proteins [6,7]. BUT has been the most widely studied SCFA and has been reported to have specific health benefits [8].…”
Section: Introductionmentioning
confidence: 99%
“…Inflammation is a complicated process which is regulated by a series of inflammatory mediators and cytokines [1]. Accumulating evidences have confirmed that pro-inflammatory cytokines, such as TNF-α and IL-6, are able to induce inflammatory responses and aggravate the development of inflammation [28]. In response to LPS, proinflammatory cytokines, such as TNF-α and IL-6, are often overproduced.…”
Section: Cpt Inhibited Lps-induced Il-6 and Tnf-α Release And Calciummentioning
confidence: 99%
“…We have also shown that FKK5 and FKK6 interact directly with PXR LBD and result in its activation. Thus, to determine the effect of FKK5 and FKK6 on the PXR-TLR4-NF-κB signaling pathway, we used PXR-transfected Caco-2 cells and exposed these cells to FKK5 and 6 since undifferentiated Caco-2 cells inherently have low PXR expression (not detected) but relatively higher TLR4 expression and are excellent in vitro models for the study of enterocyte function [36][37][38][39] . FKK5 and FKK6 down-regulates TLR4 (0.39-fold and 0.49-fold, respectively) but up-regulates CYP3A4 (3.7-fold and 3.29-fold, respectively) and MDR1 (5.12-fold and 6.45-fold, respectively) mRNA expression ( Fig.…”
Section: Characterization Of Fkk5 and Fkk6 On Pxr-tlr4 And Nf-κb Signmentioning
confidence: 99%
“…To further characterize the anti-inflammatory effects of FKK5 and 6 on human intestinal cells and tissue, we first determined their effects on Caco-2 cell monolayers. These cells were well-established models to study intestinal cell differentiation and physiology, specifically under conditions of inflammatory stimuli 38 . Differentiated Caco-2 cells via long term culture have heightened PXR expression 40 .…”
Section: Characterization Of Fkk5 and Fkk6 In Human Colon Cancer Cellmentioning
confidence: 99%